Implementasi Metode Certainty Factor Pada Sistem Pakar Untuk Mendiagnosis Gangguan Mental Berbasis Android - Nurdiansah; Cucut Cucut Susanto; Husain T; Irmawati; Akbar Bahtiar (Computer Science Research and Its Development Journal, 2023)
Good mental health is a condition when our mind is in a state of calm and calm, allowing us to enjoy everyday life and appreciate others around us. The importance of mental health for life because it can affect how a person thinks. Mental disorders can change the way a person handles stress, relates to others, makes choices, and triggers the desire to hurt oneself. In this study, the author intends to design and build an expert system to diagnose android-based mental disorders using the certainty factor method. The certainty factor method is a method used to measure something whether it is certain or uncertain in diagnosing and identifying a problem. In whitebox testing, conclusions are drawn, from the overall results of testing the applications made are free from logical errors, this can be seen from the results of calculations for the number of Cyclomatic Complexity (CC) is 12, Region = 12 and IndependentPath = 12, all values are the same. In the blackbox testing, conclusions are drawn, the overall results of the input and output testing of the application that are made are in accordance with the desired specifications. a value of 73% means the system can work well.